(untitled) (Heritage, 2023)
In The Prince with the Sad Eyes, the short story that we will here interpret as a parable in the context of Jung’s theory of archetypes, Andrić shows a woman torn between her real and idealized partner, and her suffering as a consequence of a lack of discernment in the matters of the heart, a lack of self-knowledge, and most of all, the influences of the archetypes of the collective unconscious—the animus and the shadow. Andrić thematizes projection as a psychological mechanism of falling in love, which rules interpersonal relationships in other contexts, too. Through this woman’s infatuation with the prince, Andrić sheds light on phenomena that take place between men and women every day: projecting, expecting, and disappointment experienced as betrayal. One cannot live with the animus, the archetypal figure responsible for falling in love: once a relationship becomes reality (sexuality is here a metonymic replacement for the whole of their real life, the reality of a relationship) all projections start disappearing and in most cases, are replaced with their negative counterpart, as archetypes are essentially dual in meaning. In a parable about the permanent misunderstanding between sexes in the process of falling in love, Andrić uses biblical signals (the tree of knowledge, miraculous healing, the genre of the parable) to point to the wrongness of the depicted world, that is the imaginary heaven, pursued in the wrong way and in the wrong place.